The Demand and Supply Sides of Accountability in Local Government Authorities in Tanzania. (1st November 2020) - Kessy, Ambrose T.
Abstract : Accountability and transparency have been on the top of lists of the agenda about local governance. Unfortunately, a significant number of studies have tended to view accountability through the traditional model of public administration (supply side of accountability) at the expense of the demand side of accountability. Based on the experience with decentralization in Tanzania for the past four decades, this article argues that both the demand and supply sides are important for effective service delivery by local governments. In this arrangement, the fundamental principle of democracy is attained when citizens have the right to demand accountability and public officials are held accountable. The demand side, which is bottom up driven by non–state actors, or the supply side, which encompasses legal and fiscal governmental checks and balances may lead to effective local good governance. This article is based on these assumptions and therefore attempts to discuss the main avenues and challenges for exercising effective supply and demand sides of accountability in local governments in Tanzania. The study seeks to answer the question of how the demand and supply sides of accountability have been implemented in Tanzania, regarding local governments.